Capecitabine Monotherapy is Efficient and Safe in All Line Settings in Patients with Metastatic and Advanced Breast Cancer - Amari, Masakazu; Ishida, Takanori; Takeda, Motohiro; Ohuchi, Noriaki (Japanese journal of clinical oncology, 2010)
Objective Capecitabine is effective and well tolerated in patients with anthracycline- and/or taxane-pre-treated metastatic breast cancer. We compared the efficacy and safety of capecitabine monotherapy between 1st, 2nd, 3rd and ≥4th line settings for advanced and metastatic breast cancer pre-treated with/without anthracycline and taxanes. Methods Subjects comprised 84 patients with histologically confirmed advanced or metastatic breast cancer and at least one measurable metastatic lesion. We evaluated time to disease progression (TTP), response rate (RR) and clinical benefit rate (CBR) for 1st (n = 17), 2nd (n = 28), 3rd (n = 23) and ≥4th (n = 16) line setting treatments of capecitabine monotherapy. Results Median number of cycles of capecitabine monotherapy was 12 cycles in 1st line, 11 cycles in 2nd line, 9 cycles in 3rd line and 11 cycles in ≥4th line. RR and CBR were 23.5% and 58.8% in 1st line, 21.4% and 53.6% in 2nd line, 21.7% and 52.2% in 3rd line, and 18.8% and 50.0% in ≥4th line, respectively. No significant differences in TTP were seen between each line setting (P = 0.843). Conclusions Capecitabine monotherapy is effective and well tolerated in all line settings of chemotherapy in patients with metastatic or advanced breast cancer, and is suitable for outpatient therapy.